Cobalt alkyl complexes of a new family of chiral 1,3-Bis(2-pyridylimino)isoindolates and their application in asymmetric hydrosilylation - Sauer, Désirée C.; Wadepohl, Hubert; Gade, Lutz H. (Inorganic chemistry, 2012)
Synopsis: A new family of chiral 1,3-bis(2-pyridylimino)isoindolate ligands with various substitution patterns was prepared using achiral starting materials. Their cobalt alkyl complexes were synthesized and characterized. The application of this enantiomerically pure compounds in the asymmetric hydrosilylation of ketones was tested giving the corresponding alcohols in high yields and enantioselectivity.
Gesehen am 13.09.2018